Pengembangan Media Pembelajaran Quiz Interaktif Berbantuan Software Articulate Storylane 3 Untuk Meningkatkan Hasil Belajar Siswa pada Mata Pelajaran Instalasi Penerangan Listrik Kelas XI di SMK Negeri 3 Surabaya - Oky Juan Saputra; Subuh Isnur Haryudo; Fendi Achmad; Rina Harimurti (Politeknik Kampar, 2023)
This research was carried out because the learning activities for Class XI Electrical Lighting Installation at SMK Negeri 3 Surabaya were still teacher-centred. For this reason, learning media is needed that can help students play a more active, independent role and can improve student learning outcomes. The method used in this research is 4D type R&D which consists of four stages, namely design, Define, Developed, and Dissaminate. This research aims to produce an interactive quiz learning media assisted by articulated storyline 3 software that is valid, practical and effective. The research design applied was an experimental non-equivalent control group design. The research subjects were 30 students in class XI TITL 1 and TITL 2 each. This research was carried out in the even semester 2022/2023 using an independent curriculum and a Problem Based Learning learning model. Data collection techniques use validation sheets, response questionnaires, and multiple choice tests. The learning media validation results obtained with an average of 89.68% can be categorized as very valid. In the practical aspect, in terms of the student response questionnaire, the average rating was 84%, so it can be divided into very practical. Aspects of effectiveness were tested using the Wilcoxon test and T-test. In the realm of knowledge, attitudes and skills both obtained a significance value (2-tailed) of 0.00 < 0.05, therefore it can be concluded that there was an increase in the knowledge, attitudes and skills values ??of the experimental class compared to the control class. The conclusion is that the interactive quiz learning media assisted by articulated storyline 3 software in the Class XI Electrical Lighting Installation subject that was developed can be verified as suitable for use at SMK Negeri 3 Surabaya.